The Effect of Service Quality on Patient Satisfaction in Hospitalization at Home Makassar's Laburan Baji Regional General Hospital during the Covid-19 Pandemic - Susanti, Anggriani; Razak, Amran; Muchlis, Nurmiati (PT.Mantaya Idea Batara, 2021)
The COVID-19 pandemic requires hospitals as health service providers to be able to provide maximum service to maintain good service quality. This study aims to determine the effect of service quality on Inpatient Satisfaction at Labuang Baji Hospital Makassar During the Covid-19 Pandemic. The type of research used is quantitative research with a cross sectional study design. The population in the study of this is the patient care hospitalized in RSUD Labuang Baji Makassar as many as 5,448 patients. The number of samples were used in the study as many as 70 people with the determination of a large sample of receipts formula Lammeshow and sampling techniques done in purposive sampling. Methods of data collection using a questionnaire. Data analysis was performed by univariate , bivariate with chi-square test. Results of the study show that there is the influence of the quality of service based on tangibles (p value = 0.000), realiability (p value = 0.000), responsiveness (p value 0.000 ) and assurance (p value = 0.000) towards satisfaction patient care inpatient in hospital Labuang Baji Makassar on past pandemics Covid-19. It is recommended for nurses to spend special time communicating with patients, giving attention and enthusiasm to patients so that they recover quickly.